Chapter A Prospective Sustainability Indicator for Pension Systems - Culotta, Fabrizio (Proceedings e report, 2021)
This work proposes an informative system to monitor pension systems by integrating pension and labor market statistics. This more comprehensive system is used to build an indicator to measure prospectively the sustainability of pension systems. The set of indicators is divided into two groups, each tracking pension contributions and payments flows. Each flow is composed by the product of three statistics: a statistics for the extensive margin, i.e. how many contributors and retirees, one for the intensive margin, i.e. how much workers contribute and pensioners receive pensions, and one for the durational margin, i.e. for how long workers contribute and retirees receive pensions. As such, the statistical content is coherent with the set of pension indicators considered by Eurostat and OECD. Statistics are extracted from Eurostat database and ensure cross-country comparability. The advantage of this approach is twofold. Firstly, it allows reflecting specificities of each pension regimes, characterized by own specific contribution rules and pension formulas, without explicitly account for them. Secondly, it allows to relate the assessment of sustainability of pension systems to the dynamics of labor markets since it explicitly takes into account the distribution of wages, the duration of working life, the distribution of old-age pensions and the life expectancy at retirement. An application on a pool of seven European countries (Austria, Finland, France, Germany, Italy, the Netherlands) is provided for the period 2015 - 2019. The indicator for the prospective sustainability of pension systems is compared across two other alternatives to stress the contribution of each margin. These alternatives are then compared with a benchmark indicator and their correlations are measured.